THE INTEGRATION OF ARTIFICIAL INTELLIGENCE IN LANGUAGE LEARNING: A REVIEW OF CURRENT STUDIES - Vilya Lakstian Catra Mulia (2025)
The advancement of Artificial Intelligence (AI) has introduced transformative changes in language learning. This paper presents a literature-based analysis of AI integration in language education, focusing on recent scholarly works published in the last three years. The author analyzed peer-reviewed articles that were published and indexed in well-known scientific publication databases to identify trends, benefits, and challenges. The publications show that there was an increase in the studies on AI in language learning. The applications include chatbots, intelligent tutoring systems, and adaptive platforms to personalize learning and enhance language skills. AI for language learning gives several benefits, such as increased engagement, motivation, real-time feedback, and support for autonomous learning. However, the use of AI in language learning triggers some issues, including accessibility issues, teacher readiness, data privacy, algorithmic bias, overdependence, and plagiarism. In conclusion, AI facilitates transformative language education, but it requires training, ethical standards, and a balanced approach between technology and human interaction.